HOSPITAL INFECTION CONTROL IN CAMBODIA - Pilsczek, Florian H (Pakistan Journal of Physiology, 2017)
Background: Hospital infection control and research is established in most large hospitals in industrialised nations. Cambodia is a low-income country in Southeast Asia. Methods: Published infection control studies in Cambodia are reviewed in this study, and observational study data from a hospital in Cambodia are reported. Results: No studies regarding the transmission of helminthic infections (e.g., Ascaris lumbricoides), malaria, vector-borne viral infections (e.g., Dengue), or food borne diseases (e.g., Entamoeba histolytica) in hospital were identified. In the studied hospital airborne transmission precautions were limited to use of surgical masks. Contact precautions for diarrhoea and droplet precautions for meningitis were not used. Sharps container and educational wall posters were used. Safe needle handling procedures were limited and intravenous medications were administered by trainee nurses. Conclusion: Potential routes of transmission of Mycobacterium tuberculosis among patients and from patients to healthcare workers and visitors were observed. Keywords: hospital infection control, Cambodia, low-income country Pak J Physiol 2017;13(2):29–33